EFEKTIVITAS PROGRAM PEMBERDAYAAN EKONOMI MASYARAKAT DESA LIKWATANG KECAMATAN ALOR TENGAH UTARA - Mahalita S. Moban; Loriance Tonu Weni; Salmon Weni Gati; Petrus Mau Tellu Dony (JOURNAL OF COMMUNITY DEDICATION, 2026)
The purpose of this study is to determine the effectiveness program in Likwatang village. This study uses Observation and interview Methods with a descriptive qualitative approach. This study was conducted at the Likwatang Village Office. The informant in this interview was the Head of the Likwatang Village. The result of this study indicate that in the village there is economic empowerment of the local community so that more optimal handling is needed. The strategy used by the village head is to approach the community in order to create comfort for the village and prevent further economic empowerment. However, the community continues to carry out their daily lives without economic empowerment occurring. This study emphasized the importance of cooperation between village management and the community so that the problems that occur do not just pass away but can be resolved through cooperation between the village and the local community.